2022
DOI: 10.3390/microorganisms10091711
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Acanthamoeba from Acanthamoeba Keratitis Mouse Model Using Acanthamoeba-Specific Antibodies

Abstract: Although the prevalence of Acanthamoeba keratitis (AK) is rare, its incidence in contact lens wearers has increased. Acanthamoeba infections can lead to the loss of vision if the diagnosis and treatment are delayed. In this study, we investigated the diagnostic potential of two antibodies raised against the adenylyl cyclase-associated protein (ACAP) and periplasmic binding protein (PBP) of A. castellanii in the AK mouse model. The specificity of ACAP and PBP antibodies to Acanthamoeba was confirmed by immunocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Previously, we reported that Acanthamoeba antigens in tears and eyeball lysates of the AK mouse model were detected by adenylyl cyclase-associated protein (ACAP) and periplasmic binding protein (PBP) antibodies [28]. Interestingly, Acanthamoeba antigens in the AK mice samples were detected to a greater extent by the CM antibody in comparison to the ACAP and PBP reported in our previous study.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Previously, we reported that Acanthamoeba antigens in tears and eyeball lysates of the AK mouse model were detected by adenylyl cyclase-associated protein (ACAP) and periplasmic binding protein (PBP) antibodies [28]. Interestingly, Acanthamoeba antigens in the AK mice samples were detected to a greater extent by the CM antibody in comparison to the ACAP and PBP reported in our previous study.…”
Section: Discussionmentioning
confidence: 46%
“…To address this limitation, we recently reported the diagnostic potential of Acanthamoeba-specific adenylyl cyclase-associated protein (ACAP) and periplasmic binding protein (PBP) antibodies using the tears and eyeball lysates acquired from the AK mouse model [28]. While this study demonstrated that non-invasive diagnosis of AK via antibodybased methods is feasible, both ACAP and PBP antibodies weakly interacted with the murine samples.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on target structures in Acanthamoeba spp. These potential targets for antibodies may aid in diagnosis in the future: inosine-uridine preferring nucleoside hydrolase (IPNH), chorismite mutase (CM), carboxylesterase, adenylyl cyclaseassociated protein (ACAP), and periplasmic binding protein (PBP) [65][66][67][68][69]. Additional studies have demonstrated the utility of CM and ACAP/PBP antibodies in AK diagnosis in mouse and rabbit animal models, respectively [69,70].…”
Section: Antibodymentioning
confidence: 99%
“…These potential targets for antibodies may aid in diagnosis in the future: inosine-uridine preferring nucleoside hydrolase (IPNH), chorismite mutase (CM), carboxylesterase, adenylyl cyclaseassociated protein (ACAP), and periplasmic binding protein (PBP) [65][66][67][68][69]. Additional studies have demonstrated the utility of CM and ACAP/PBP antibodies in AK diagnosis in mouse and rabbit animal models, respectively [69,70]. Antibody-based tests hold potential in the diagnosis of AK but still require further investigation and development prior to their widespread use.…”
Section: Antibodymentioning
confidence: 99%